PENGARUH TARIF PAJAK, MEKANISME PEMBAYARAN PAJAK, SANKSI PAJAK DAN KESADARAN MEMBAYAR PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA PATI - Silvana Rahmawati; Zulfikar (JURNAL ILMIAH EDUNOMIKA, 2026)
Taxes are the main source of state revenue and play a crucial role in infrastructure development and public service provision. MSMEs, as the dominant business sector in Indonesia, have significant potential to contribute to tax revenue. However, the tax compliance level of MSME taxpayers remains low. This study aims to analyze the effect of tax rates, tax payment mechanisms, tax sanctions, and tax awareness on the tax compliance of MSMEs in Pati City. This research uses a quantitative approach with primary data collected through questionnaires from 108 MSME respondents. The sampling technique used is convenience sampling. The results show that all four independent variables have a positive and significant effect on taxpayer compliance. This means that lower tax rates, easier and more transparent payment mechanisms, strict tax sanctions, and high awareness among taxpayers contribute to improved MSME tax compliance. Keywords : Tax, MSMEs, Tax Rate, Tax Sanction, Taxpayer Compliance, Tax Awareness, Pati City